Ende Rahim Pancasila: Embrio Pancasila dalam Nilai-nilai Budaya Masyarakat Ende-Lio - Adrianus Yohanes Mai; Amandus Benediktus Seran Klau; Otto Gusti Ndegong Madung (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Pancasila is the crystallization of the values of culture, religion and customs of the Indonesian nation. Knowing the history of its birth and also the socio-cultural bedground are essential to fully understand Pancasila. Ende is a historical place because it was in this place where Sukarno contemplated the Indonesian values that was revealed in Pancasila. This study analyzes how the values of the Ende-Lio cultural community as the embryo of the birth of Pancasila. The method used in this study is a qualitative ethnographic method in which five points of Pancasila are analyzed based on the cultural values of the Ende-Lio community. Based on this study, it can be concluded that every item of Pancasila is basically contained in the cultural values of the Ende-Lio community.